Effectiveness of protective foot and forearm guards in Taekwondo - Ramazanoglu, N. (Archives of Budo, 2012)
The aim of this study was to evaluate the effectiveness of forearm guards and foot protectors which are the main impact targets for kicks in Taekwondo.